2022
DOI: 10.1037/pas0001091
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cross-informant discrepancies in aggressive and prosocial behavior: A latent difference score analysis.

Abstract: Cross-informant discrepancies (CIDs) in youth behavior are common. Given that these same behaviors often show or are perceived to show gender differences, it is important to understand how informant perceptions and their discrepancies are affected by gender. In n = 1,048 (51% male) Grade 5 (age 11) Swiss youth, self-versus teacher (n = 261) CIDs were explored using latent difference score (LDS) modeling. CIDs in prosociality (β = −.15) and aggression (β = .14) were predicted by child gender after adjusting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…We were unable to find support for the proposed five-factor structure of the SDQ, which is not an uncommon finding [ 3 , 15 , 32 , 34 ]. Previous confirmatory factor analyses conducted on the SDQ using MCS data have supported the five-factor structure at ages 5, 7, 11, and 14, but not age 17 [ 32 34 ], calling into question the acceptability of the SDQ factor structure in older adolescents.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We were unable to find support for the proposed five-factor structure of the SDQ, which is not an uncommon finding [ 3 , 15 , 32 , 34 ]. Previous confirmatory factor analyses conducted on the SDQ using MCS data have supported the five-factor structure at ages 5, 7, 11, and 14, but not age 17 [ 32 34 ], calling into question the acceptability of the SDQ factor structure in older adolescents.…”
Section: Discussionmentioning
confidence: 79%
“…We were unable to find support for the proposed five-factor structure of the SDQ, which is not an uncommon finding [ 3 , 15 , 32 , 34 ]. Previous confirmatory factor analyses conducted on the SDQ using MCS data have supported the five-factor structure at ages 5, 7, 11, and 14, but not age 17 [ 32 34 ], calling into question the acceptability of the SDQ factor structure in older adolescents. Despite this, most research using the SDQ examines individual mean scores of the subscales, therefore the approach taken in this study to examine factors independently can be considered valid.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This could be related to the fact that items used to measure pro-sociality (e.g., kindness, consideration) are more analogous with female identity, and therefore possibly underreported by male adolescents. A recent study in a general population school sample of younger adolescents (median age 11 years) in Switzerland examined teacher-child informant discrepancies for pro-social behaviour, nding that teachers reported less prosociality in both sexes, but to a greater extent in males (Murray, Nivette, et al, 2022). Although this effect was in the opposite direction, as parents reported more pro-sociality than adolescents in our study, together, this suggests that informant discrepancies for pro-sociality are likely to be greater in males, perhaps due to a general bias within society associating pro-sociality with female identity.…”
Section: Conditional Effectsmentioning
confidence: 99%
“…We are taking a multiinformant perspective given that prior research has found discrepancies in reported levels of prosociality depending on the informant. For instance, a recent study on cross-informant discrepancies conducted in the here used sample found that young people report higher levels of prosociality than attributed to them by their teachers (Murray et al, 2022). To explore a potential mechanism by which prosociality and aggressive behaviors may become linked, we further investigated whether peer relationships mediated the associations between prosociality and bullying perpetration as well as aggressive behaviors.…”
Section: Introductionmentioning
confidence: 97%